Strategic reconfiguration as a component of the potential of participating enterprises in the implementation of public-private partnership projects - Kolisnyk, H. (Ways to Improve Construction Efficiency, 2024)
In the modern conditions of the economic development of the state and the private sector, there is a need for cooperation for the implementation of socially significant projects. One of the effective mechanisms of such cooperation is public-private partnership (PPP). The successful implementation of PPP projects largely depends on the ability of enterprises to make strategic adjustments, which involves flexibility, adaptability and the ability to innovate. The results of the study can be useful for managers of enterprises participating in PPP projects, as well as for representatives of state bodies responsible for the development of public-private partnerships. They will help to understand the importance of strategic reconfiguration and its impact on increasing the competitiveness and sustainability of enterprises in a dynamic market environment. Strategic reconfiguration of components of the potential of enterprises participating in the implementation of public-private partnership projects is a relevant topic in the modern economic environment. This research work is aimed at analyzing the strategies used by enterprises to adapt to the conditions of implementation of such projects, considering their internal potential and capacity for innovative and transformational changes. The abstract discusses key aspects of strategic management, including the impact of the regulatory environment, financial and organizational aspects of the preparation and implementation of PPP projects. The study also emphasizes the importance of strengthening partnerships between the public and private sectors, contributing to the creation of sustainable investment projects and increasing the competitiveness of economic participants.